Nine weeks versus 1 year adjuvant trastuzumab in patients with early breast cancer: an observational study by the Turkish Oncology Group (TOG) - (:unkn) unknown (SPRINGER JAPAN KK, 2015)
Background Optimal duration of adjuvant trastuzumab in early breast cancer is an unresolved issue. In this observational study, we compared the outcome of 9 weeks and 1 year adjuvant trastuzumab in early breast cancer patients in Turkey. Methods Records of 680 patients with HER2-positive early breast cancer who received adjuvant trastuzumab plus chemotherapy were obtained and patients were followed up to compare the disease-free survival (DFS) outcome of 9 weeks versus 1 year trastuzumab. Results Nine weeks and 1 year trastuzumab was given to 202 (29.7 %) and 478 (70.3 %) patients, respectively. There was a significantly lower rate of patients with negative lymph nodes in the 9-week trastuzumab group. At median 3 years of follow-up from the date of starting trastuzumab, the DFS rates were 88.6 and 85.6 %, respectively (p = 0.670). When adjusted for all the prognostic factors that were significant on univariate analysis, again there was no significant difference in DFS between the groups (HR 0.675; 95 % CI 0.370-1.231; p = 0.200). Cardiac toxicity defined as a >= 15 % decrease in LVEF was significantly higher in the 1-year trastuzumab group (1.88 % versus none for 1-year and 9-week trastuzumab groups, respectively; p = 0.050). Conclusion The results of this observational study suggest that DFS outcome of 9 weeks of adjuvant trastuzumab may be comparable to 1 year adjuvant trastuzumab: this needs confirmation by randomized trials.
Keywords: Adjuvant treatment; Nine weeks trastuzumab; Cardiotoxicity; Early breast cancer; CHEMOTHERAPY; XENOGRAFTS; ANTIBODY; RECEPTOR; THERAPY